Levels and Health Risk Assessment of Heavy Metals in Soil, Water, and Vegetables of Dar es Salaam, Tanzania - David Sylvester Kacholi; Minati Sahu (Journal of Chemistry)
This study assesses heavy metals’ levels in water, soil, and vegetables (Ipomoea batatas (Matembele), Amaranthus hybridus (Mchicha), Abelmoschus esculentus (Bamia), and Solanum melongena (Bilinganya)) from the Chang’ombe police garden located in Temeke district, Tanzania. Also, it examines potential health risks from consumption of the vegetables. The samples of soils, water, and vegetables were randomly collected, processed, and analyzed for heavy metals using Atomic Absorption Spectrophotometry. The heavy metals’ levels in soil, water, and vegetables were in the order of Fe > Zn > Pb > Cu. Among the vegetables, I. batatas had highest heavy metal content followed by A. hybridus, S. melongena, and A. esculentus. The average daily intake for Pb (63 mg/person/day) was above the permissible maximum tolerable daily intake of 0.21 mg/person/day endorsed by WHO/FAO. Hazard quotient of Pb for I. batatas (7.12) and A. hybridus (2.46) as well as the hazard indices of I. batatas (7.99) and A. hybridus (2.88) exceeded unity, signifying presence of health risks from consumption of the vegetables. This study recommends regular monitoring of heavy metals in soils, water, and foodstuffs to prevent excessive accrual in food chain.